OPTIMALISASI PARTISIPASI PUBLIK DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN MELALUI CIVIC PARTICIPATION INDEX - Gunawan Widjaja; Wagiman Martedjo; Lisno Setiawan (The Juris, 2025)
Law Number 13 of 2022, which serves as the Second Amendment to Law Number 12 of 2011, strengthens public involvement and participation in all stages of the legislative process, from planning to enactment. However, according to the development of public participation as reflected in the Civic Participation Index from 2019 to 2024 published by the World Justice Project, Indonesia has experienced a downward trend. Several challenges to public participation include the lack of public awareness of their participatory rights, limited access to information, and the absence of effective mechanisms for gathering public input. This study employs a normative juridical method with a statute approach to analyze existing regulations and their implementation (best practices) in accordance with international standards, using a comparative study of countries with higher civic participation index levels. The data were collected from secondary sources, including primary legal materials, secondary legal materials, and tertiary legal materials. This study is of significant urgency as it can provide practical recommendations for the development of more effective technical guidelines on public participation as mandated by Law Number 13 of 2022.